IN-VITRO HYPOGLYCEMIC EVALUATION OF FRACTIONS OF HYDRO-ACOHOLIC EXTRACT OF HEARTWOOD OF TECOMELLA UNDULATA LINN. - Rohilla, Ruby; Garg, Chanchal; Garg, Munish (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To screen Î±-amylase and Î±-glucosidase inhibitors from the different fractions of crude hydro-alcoholic extract of heartwood of Tecomella undulata Linn. Methods: Four fractions of crude hydro-alcoholic extract of heartwood of plant were used for in-vitro inhibitory assays against digestive enzymes: Î±-amylase and Î±-glucosidase. For assay, different concentrations (20, 40, 60, 80, 100 Âµg/ml) were used for all fractions. Standard protocol was used for preliminary phytochemical screening of different bioactive components present in all fractions. Results: The fractions have shown moderate to highest inhibitory activity against both enzymes. But, the strong inhibition was revealed by acetone fraction against Î±-amylase with very minimal inhibitory concentrations at IC50 values when compared with a standard drug acarbose. Several medicinally active phytocomponents such as flavanoids, saponin, anthraquinones, tannins, triterpenoids and phenols were observed in all studied fractions. Conclusion: The different fractions prepared from crude hydro-alcoholic extract of heartwood of plant are capable of inhibiting Î±-amylase and Î±-glucosidase and it can be concluded that heartwood of Tecomella undulata Linn. is partially active against postprandial hyperglycemia, thus diabetes mellitus. Keywords: Tecomella undulata Linn., Diabetes mellitus, Î±-Amylase, Î±-Glucosidase. Â 